Exploring the Impact of Digital Media in Pesantren-Based Education: Enhancing Islamic Studies Learning and Fostering Character Development among Student - Maulana, Muhammad Miftahul (JURNAL ISLAM NUSANTARA, 2024)
The aims of this study is to examine how digital tools can enhance the educational experience and contribute to the moral and ethical development of students. This article explores the use of digital media in Islamic education learning to strengthen the character of students at school. A descriptive qualitative research method was employed, with data collected through observations, interviews, and documentation. Data analysis utilized data triangulation to ensure the reliability and validity of the findings. The research results indicate that the integration of digital media in Islamic boarding schools positively impacts learning outcomes by increasing student engagement, comprehension, and retention. However, the study also identifies challenges such as the need for adequate technological infrastructure and teacher training, as well as the importance of aligning digital content with Islamic values. Best practices include regular professional development for educators, a balanced approach combining traditional and digital methods, and ongoing evaluation of digital resources.